Pharmacogenetics and individual responses to treatment of hyperglycemia in type 2 diabetes. Issue 10 (October 2015) - Engelbrechtsen, Line; Andersson, Ehm; Roepstorff, Soeren; Hansen, Torben; Vestergaard, Henrik
<x xml:space="preserve">Abstract</x> The aim of this study was to summarize current knowledge and provide perspectives on the relationships between human genetic variants, type 2 diabetes, antidiabetic treatment, and disease progression. Type 2 diabetes is a complex disease with clear-cut diagnostic criteria and treatment guidelines. Yet, the interindividual response to therapy and slope of disease progression varies markedly among patients with type 2 diabetes. Gene–gene, gene–environment, and gene–treatment interactions may explain some of the variation in disease progression. Several genetic variants have been suggested to be associated with response to antidiabetic drugs. Some are present in drug receptors or drug metabolizers (OCT genes, KCNJ11, ABCC8, and CYP2C9). Numerous type 2 diabetes risk variants have been identified, but genetic risk score models applying these variants have failed to identify 'disease progressors' among patients with diabetes. Although genetic risk scores are based on a few known loci and only explain a fraction of the heritability of type 2 diabetes, it seems that the genes responsible for the development of diabetes may not be the same driving disease progression after the diagnosis has been made. Pharmacogenetic interactions explain some of the interindividual variation in responses to antidiabetic treatment and may provide the foundation for future genotype-based treatment standards.